Angiogenesis, Osseointegration, and Antibacterial Applications of Polyelectrolyte Multilayer Coatings Incorporated With Silver/Strontium Containing Mesoporous Bioactive Glass on 316L Stainless Steel - Kuo, Yi-Jie; Chen, Chia-Hsien; Dash, Pranjyan; Lin, Yu-Chien; Hsu, Chih-Wei; Shih, Shao-Ju; Chung, Ren-Jei (Frontiers in Bioengineering and Biotechnology, 2022)
The main causes for failure in implant surgery are prolonged exposure of implants or wound and tissue ischemia. Bacterial infection caused by the surrounding medical environment and equipment is also a major risk factor. The medical risk would be greatly reduced if we could develop an implant coating to guide tissue growth and promote antibacterial activity. Mesoporous bioactive glasses are mainly silicates with good osteoinductivity and have been used in medical dentistry and orthopedics for several decades. Strontium ions and silver ions could plausibly be incorporated into bioactive glass to achieve the required function. Strontium ions are trace elements in human bone that have been proposed to promote osseointegration and angiogenesis. Silver ions can cause bacterial apoptosis through surface charge imbalance after bonding to the cell membrane. In this study, functional polyelectrolyte multilayer (PEM) coatings were adhered to 316L stainless steel (SS) by spin coating. The multilayer film was composed of biocompatible and biodegradable collagen as a positively charged layer, γ-polyglutamic acid (γ-PGA) as a negatively charged layer. Chitosan was incorporated to the 11th positively charged layer as a stabilizing barrier. Spray pyrolysis prepared mesoporous bioactive glass incorporated with silver and strontium (AgSrMBG) was added to each negatively charged layer. The PEM/AgSrMBG coating was well hydrophilic with a contact angle of 37.09°, hardness of 0.29 ± 0.09 GPa, Young’s modulus of 5.35 ± 1.55 GPa, and roughness of 374.78 ± 22.27 nm, as observed through nano-indention and white light interferometry. The coating’s antibacterial activity was sustained for one month through the inhibition zone test, and was biocompatible with rat bone marrow mesenchymal stem cells (rBMSCs) and human umbilical vein endothelial cells (HUVECs), as observed in the MTT assay. There was more hydroxyapatite precipitation on the PEM/AgSrMBG surface after being soaked in simulated body fluid (SBF), as observed by scanning electron microscopy (SEM) and X-ray diffraction (XRD). In both in vitro and in vivo tests, the PEM/AgSrMBG coating promoted angiogenesis, osseointegration, and antibacterial activity due to the sustained release of silver and strontium ions.